Sine-gordon transformations in nonequilibrium systems of Brownian particles - Skrypnik, V.I. (Український математичний журнал, 1997)
Finite volume grand canonical correlation functions of nonequilibrium systems of d-dimensional Brownian particles, interacting through a regular (long-range) pair potential with integrable first partial derivatives, are expressed in terms of the expectation values of a Gaussian random field. The initial correlation functions coincide with the Gibbs correlation functions corresponding to a more general pair long-range potential. Nonequilibrium Euclidean action is introduced, satisfying a thermodynamic stability property. Для нерівноважної багатокомпонентної системи браунівських частинок, що взаємодіють завдяки (далекосяжному) парному потенціалу з інтегровними частковими похідними другого порядку, в області скінченного об'єму кореляційні функції великого канонічного ансамблю виражені у термінах математичного сподівання функцій кількох гауссівських випадкових полів. Початкові кореляційні функції збігаються з гіббсівськими кореляційними функціями, що відповідають більш загальному парному потенціалу взаємодії. Введена нерівноважна евклідівська дія, що задовольняє умову термодинамічної стійкості.